2019
DOI: 10.1124/mol.118.114595
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Regulatory Properties of Human Adenylyl Cyclase Type 9

Abstract: Membrane-bound adenylyl cyclase (AC) isoforms have distinct regulatory mechanisms that contribute to their signaling specificity and physiologic roles. Although insight into the physiologic relevance of AC9 has progressed, the understanding of AC9 regulation is muddled with conflicting studies. Currently, modes of AC9 regulation include stimulation by Gas, protein kinase C (PKC) bII, or calcium-calmodulin kinase II (CaMKII) and inhibition by Gai/o, novel PKC isoforms, or calcium-calcineurin. Conversely, the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 63 publications
2
41
0
Order By: Relevance
“…Nevertheless, siRNA-mediated knockdown analysis indicated that both AC1 and AC9 make a small but statistically significant contribution to the overall cAMP response elicited by endogenous β2ARs ( Fig S8A ). In contrast, AC1 but not AC9 knockdown reduced the FSK-induced cAMP response ( Fig S8B ), consistent with AC9 being resistant to stimulation by FSK (Baldwin et al, 2019) and verifying specificity of the knockdowns. Considering that AC9 selectively accumulates in endosomes relative to AC1, we next investigated the hypothesis that AC9 accordingly contributes to the endosome-initiated component of the β2AR-elicited cAMP response.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Nevertheless, siRNA-mediated knockdown analysis indicated that both AC1 and AC9 make a small but statistically significant contribution to the overall cAMP response elicited by endogenous β2ARs ( Fig S8A ). In contrast, AC1 but not AC9 knockdown reduced the FSK-induced cAMP response ( Fig S8B ), consistent with AC9 being resistant to stimulation by FSK (Baldwin et al, 2019) and verifying specificity of the knockdowns. Considering that AC9 selectively accumulates in endosomes relative to AC1, we next investigated the hypothesis that AC9 accordingly contributes to the endosome-initiated component of the β2AR-elicited cAMP response.…”
Section: Resultssupporting
confidence: 71%
“…An important future goal is to identify structural and biochemical determinants of isoform-specific AC trafficking. We note that various isoform-specific protein interactions which impact other aspects of AC function are already known, with AC9 being a particularly well-studied example (Baldwin et al, 2019). Another important question for future investigation is whether regulated intracellular trafficking is unique to AC9 or is more widespread.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, analysis by isoform-specific knockdown using siRNA indicated that both AC1 and AC9 make a small but statistically significant contribution to the overall cAMP elevation elicited by activation of endogenous β2ARs. AC1 but not AC9 depletion reduced the FSK-induced cAMP response ( Figure 6—figure supplement 1 ), consistent with AC9 being relatively insensitive to stimulation by FSK ( Baldwin et al, 2019 ) and verifying specificity of the knockdown approach. Considering that AC9 selectively accumulates in endosomes relative to AC1, we next investigated the hypothesis that AC9 also selectively contributes to the endosome-initiated component of the β2AR-elicited cellular cAMP response.…”
Section: Resultssupporting
confidence: 69%
“…To test this, we applied the diterpene drug forskolin (FSK) to stimulate cytoplasmic cAMP production independently from the receptor or Gs. While AC9 is relatively insensitive to activation by FSK, other AC isoforms that are major contributors to cAMP production in HEK293 cells (such as AC3 and AC6) are sensitive, making FSK an effective stimulus of overall cAMP elevation ( Baldwin et al, 2019 ; Soto-Velasquez et al, 2018 ). FSK did not cause detectable internalization of either HA-β2AR or Flag-AC9 assessed by imaging ( Figure 4—figure supplement 1A,C,D,I ) or surface biotinylation ( Figure 4—figure supplement 1E,F ).…”
Section: Resultsmentioning
confidence: 99%